THE EFFECT OF PRODUCT QUALITY AND PRICE ON CONSUMER SATISFACTION WITH PURCHASE DECISIONS AS AN INTERVENING VARIABLE (CASE STUDY OF NAZWA ASSORTED CAKES) - Satria Tirtayasa (Jurnal Mantik, 2022)
The authors aim to research to determine and analyze the effect of product quality and price on consumer satisfaction through purchasing decisions (Nazwa Aneka Kue case study) The method used is an associative and quantitative approach. The population in this study is Nazwa Aneka Kue consumers with an unknown population, and in determining the sample using the formula wibisono the sample size of 100 people is obtained. Data collection techniques used in this study used a questionnaire/questionnaire. Data analysis techniques in this study used Path Analysis, Classic Assumption Test, Hypothesis Test (t Test and f Test), and Determination Coefficient. Data processing in this study uses the IBM SPSS software program (Statistics Package for the Social Sciences) version 23. The results of this study indicate that partially product quality has a significant effect on customer satisfaction, the price has a significant effect on customer satisfaction, product quality has a significant effect on purchasing decisions, prices influence purchasing decisions, and purchasing decisions significantly influence customer satisfaction, product quality, and prices simultaneously and significantly influence customer satisfaction, product quality has a simultaneous and significant influence on consumer satisfaction through purchasing decisions, prices have a simultaneous influence and significant impact on customer satisfaction through purchasing decisions.